The Law of Marriage and Tabattul According to the Perspective of Imam Ibn Taymiyah - Kholil Ahmad Sabili; Fakhrurazi; Usman Alfarisi; Defril Amin; Najla Hafizah (Muwafaqat: Journal of Islamic Law, 2025)
Imam Ibn Taymiyyah was a great scholar with the title of Shaykhul Islam who played a role in purifying the teachings of Islam from khurafat and deviations. However, he never married in his life. This thesis discusses Imam Ibn Taymiyyah's views on the law of marriage and tabattul in Islam through library research. This research formulates two main problems: 1) Imam Ibn Taymiyyah's opinion on the law of marriage, and 2) His view on tabattul. The aim is to describe the law of marriage and tabattul in his thought based on existing sources. The results show that according to Imam Ibn Taymiyyah, the law of marriage is basically sunnah, in line with the opinion of the majority of scholars. If someone is worried about falling into adultery, marriage is preferred to the obligatory Hajj. Marriage is seen as a means of maintaining personal chastity and fulfilling human nature. Meanwhile, tabattul, which is the attitude of avoiding marriage absolutely, is not recommended because Allah SWT has ordered marriage as a good for His servants. Imam Ibn Taymiyyah emphasized that avoiding marriage without a justifiable reason could mean forbidding something that Allah has already legalized. Therefore, Islam recommends marriage as part of worship and a more perfect life.